Teach for All - Drenttel, William, (SAGE Knowledge. Cases., 2017)
By its November 2011 annual conference in Mumbai, Teach For Alls network consisted of 23 national partner organizations. Network members came from all over the globe, representing an eclectic group of countries. From Estonia, with a population of 1.3 million and near universal literacy, to India, with more than 900 times more people than Estonia and only 75% literacy, the one thing that united the diverse network was a commitment to building an organization similar to Teach For America in their respective countries.